Controladores naturais da lagarta do cartucho do milho, no Estado do Ceará - Parasitism upon the worms of Spodoptera frugiperda was observed in three critical stage of growth of maize, in Pacajus, Ceará, Brazil. (Revista Ciência Agronômica, 2023)
RCA